2022
DOI: 10.1088/1361-6595/ac5c61
|View full text |Cite
|
Sign up to set email alerts
|

Power law fitting of the ion saturation current and the three-temperature Maxwellian EEDF in a multi-dipole confined hot cathode discharge: an experimental revisitation

Abstract: Langmuir probe diagnostics in a multi-dipole confined hot cathode discharge has been revisited with an improved sheath expansion model with fitted expansion parameters. The results show a three-Maxwellian EEDF composition also observed in previous studies using a very similar system. The dependence on neutral pressure and discharge current of each electron species are consistent with known physical processes in a multi-dipole confined hot cathode discharge. This shows that the employment of the new ion saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…In a triple-Maxwellian EEDF with a low discharge current, it is generally observed that hotter species tend to have lower densities [6]. In this study, we specifically focus on the hotter species and the cold species, as they are the primary contributors to T eff and thereby influence the kinetic effects within the plasma.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a triple-Maxwellian EEDF with a low discharge current, it is generally observed that hotter species tend to have lower densities [6]. In this study, we specifically focus on the hotter species and the cold species, as they are the primary contributors to T eff and thereby influence the kinetic effects within the plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Baalrud et al proposed a solution of augmented heating resulting from instability-enhanced collisions, originally to resolve the Langmuir's paradox but also have implication to other aspects of basic plasma physics like the determination of Bohm criterion [13]. To understand the conventional physical understanding, a pure production-loss balance model is formulated in the following [6,[15][16][17]. To streamline the relevant calculations, we can make an approximation for the total rate of primary electrons injected into the plasma as I Dis /e.…”
Section: Eedfs In Multi-dipole Confined Hot Cathode Dischargesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yip et al discovered that even when the ratio of the area of the Langmuir probe area to the chamber wall area A L /A S is less than or near (m i /(2.3m e )) 1/2 as predicted by conventional theory, a small virtual cathode can still form near the probe, affecting the I-V curve and leading to a significant error of ∼30% in electron temperature measurement [35]. Jin et al later conducted experiments in Diagnostics Test Source II (DTS-II) [23,36], as shown in figure 3(a), in argon plasma and scanned A L /A S of an ADLP ranging from 15-365 with the 2 mm diameter small probe A S unchanged and the diameter of large probe A L varying from 8-40 mm. The plasma parameters were measured by a single Langmuir probe biased with respect to the grounded chamber wall and the ADLP is floating and its two probe tips were biased with respect to each other, as shown in figures 3(b) and (c).…”
Section: Experimental Studies On the Area Limitation Of The Langmuir ...mentioning
confidence: 99%
“…The ion current 𝐼 𝑖 is then subtracted from the 𝐼-𝑉 trace and multiple Maxwellian fitting is performed, the process of which is shown in detail in reference [17]. The device where the experiments were conducted is a multi-dipole confined hot cathode source, which would be introduced in detail in the following section, and generally has several electron species due to the complicated processes of formation of the bulk electron energy distribution function (EEDF) including primary electrons injected into the device from the hot cathode, primary electrons degraded by collisions with the neutrals, secondary electrons produced by primary electrons colliding with the device's chamber wall, plasma electrons produced via impact ionization, and electron loss to the walls [18]. Therefore, the electron temperature would be fitted with single-, bi-or triple-Maxwellian fitting automatically and a collected current would be reconstructed based on the fitting results.…”
Section: Fitting Algorithmmentioning
confidence: 99%